Indigenous Communities and Settler Colonialism Land Holding, Loss and Survival in an Interconnected World - Laidlaw, Zoë.; Laidlaw, Zoë.; Lester, Alan.; Lester, Alan. (Cambridge Imperial and Post-Colonial Studies Series, 2015)
The new world created through Anglophone emigration in the 19th century has been much studied. But there have been few accounts of what this meant for the Indigenous populations. This book shows that Indigenous communities tenaciously held land in the midst of dispossession, whilst becoming interconnected through their struggles to do so.